The dead gentleman ebook - Cody, Matthew (2011)
A many-worlds adventure novel from the acclaimed author of Powerless !   The Dead Gentleman is a wild ride between parallel New York City timestreams—1901 and today. Eleven-year-old Tommy Learner is a street orphan and an unlikely protégé of the Explorers, a secret group dedicated to exploring portals—the hidden doorways to other worlds. But in the basement of an old hotel, his world collides with that of modern-day Jezebel Lemon. Now, Jezebel and Tommy must thwart the Dead Gentleman, a legendary villain whose last unconquered world is our own planet Earth, a realm where the dead stay dead—for now. Can two kids put an end to this ancient evil and his legions of Grave Walkers?